2017
DOI: 10.1128/jvi.00801-17
|View full text |Cite
|
Sign up to set email alerts
|

Role of Autophagy in HIV-1 Matrix Protein p17-Driven Lymphangiogenesis

Abstract: AIDS-related lymphomas (ARLs) are expected to increase in the future since combined antiretroviral therapy (cART) enhances the life expectancy of HIV-1-infected (HIV ϩ ) patients but does not affect the occurrence of ARLs to the same extent as that of other tumors. Lymphangiogenesis is essential in supporting growth and metastatic spreading of ARLs. HIV-1 does not infect the neoplastic B cells, but HIV-1 proteins have been hypothesized to play a key role in sustaining a prolymphangiogenic microenvironment in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…At the same time, Beclin-1 deficient mice were completely unsensitive to the pro-coagulant p17 activity, suggesting that in vivo thrombin formation following p17 injection depends on an intact autophagy pathway. Notably, we have previously demonstrated the role of autophagy in p17-driven ET-1 secretion and angiogenesis [33]. Similarly, impaired granular exocytosis has been observed after inhibition of autophagy within different cells [5,49,50].…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…At the same time, Beclin-1 deficient mice were completely unsensitive to the pro-coagulant p17 activity, suggesting that in vivo thrombin formation following p17 injection depends on an intact autophagy pathway. Notably, we have previously demonstrated the role of autophagy in p17-driven ET-1 secretion and angiogenesis [33]. Similarly, impaired granular exocytosis has been observed after inhibition of autophagy within different cells [5,49,50].…”
Section: Discussionmentioning
confidence: 64%
“…Interestingly, we demonstrated that angiogenesis induced by p17 is partly supported by the release of ET-1 and by activation of the ET-1/ET-1 B receptor axis [32]. ET-1 secretion from ECs upon p17 stimulation was found to rely on mechanisms of conventional secretory pathways regulated by autophagy both in vitro and in vivo [33].…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…It was reported that the HIV‐1 infected cells can release significant amounts of virion‐free p17, which may abnormally activate host T lymphocytes and dendritic cells, induce monocyte‐mediated inflammatory, and then is associated with AIDS pathogenesis . Moreover, p17 was found to exhibit lymphangiogenesis activity in the HIV‐1 patients . Reciprocally, anti‐p17 antibodies circulating in HIV patients can suppress or retard the AIDS progression .…”
Section: Introductionmentioning
confidence: 99%